(untitled) (American Journal of Business Management, Economics and Banking, 2025)
This article provides an in-depth analysis of Uzbekistan’s state budget planning process for 2025. The article discusses key macroeconomic projections, including an expected 6 percent growth in the state budget. Gross domestic product (GDP) is driven by industry, agriculture, and services. The government’s approach to the budget is consistent with the "Uzbekistan - 2030" strategy and is aimed at ensuring sustainable economic growth, tax reform, and budget transparency. Key policies include keeping the consolidated budget deficit below 3 percent of GDP, improving the tax base, and gradually aligning tax and budget policies with World Trade Organization (WTO) standards. The article also discusses the importance of public participation in budget planning, ensuring environmental sustainability, and implementing the principles of "green budgeting." Through these efforts, Uzbekistan aims to ensure financial stability and long-term economic development.